Aplikasi Analisis Pareto Dalam Pengendalian Inventori Bahan Baku Pada Bisnis Restoran - Pawitan, Gandhi; Paramasatya, Amithya (Jurnal Administrasi Bisnis, 2008)
Quality of the raw materials are an important factor to keep business life of the restaurant.The freshness and originality of the material should be concerned all the time.The raw materials are ordered without any planning or scheduled. There are manykind of raw materials to cook all the menu. Hence we consider only the top 10 sellingmenu during January 2006 until December 2006. These raw materials are then classifiedto group A, B, and C according to ABC analysis along with usage and investment.ABC Critical Index Analysis are then conducted to find out whether the raw materialsis critical or not toward the service to consumer. This analysis combined investmentvalue, usage value, and critical value. Raw materials that classifies for group A inABC Critical Index Analysis are considered as important raw materials, which mustalways be available. By using ABC critical index analysis group A consists of sixteentype of raw materials with usage value 83,08%, group B consists of nine type of rawmaterials with usage value 10,74%, group C consists of 9 type raw materials withusage value 6,18%.Keywords: Pareto analysis, inventory control